Mapping the environmental impacts and policy effectiveness of takeaway food industry in China - Zhang, Yuting; Wen, Zongguo (The Science of the total environment, 2022)
The takeaway food industry, involving more than 0.4 billion consumers in China, has brought mass of packaging waste and salient environmental burden. Here we mapped the distribution of takeaway food industry across China including the industry scale, diet structure and order time based on the analysis of more than 35 million takeaway food orders. The real use situation of various packaging materials in the takeaway food industry market has been clarified. The life cycle assessment of “a piece of takeaway food delivery order” has been carried out in different regions. Results show that in addition to plastic waste generation, takeaway food industry causes more types of environmental impacts. In terms of the national resource consumption, greenhouse gases emission, water pollution and health damage risk, the top 5 ranked provinces in each accounted for 44%, 48%, 43% and 49%, respectively. Under the latest Chinese plastic pollution control policy, the industry needs to reduce 1.12 million tons of non-degradable plastic packaging by the end of 2025, and 65% of the pressure is clustered in the metropolis and provincial capitals. However, without targeted and regionally differentiated plastic pollution control policies, the environmental impact control of takeaway food industry is still ineffective. It is urgent to explore the control measures applicable to different regions. Overall, packaging reduction is more effective than material substitution. [Display omitted] •Demonstrate the development laws of takeaway food industry•Map the food packaging consumption and waste generation in different regions•Calculate the life-cycle environmental impacts of takeaway food delivery orders•Predict the reduction pressure of packaging products under the latest policy•Discuss pathways' effectiveness to achieve the policy goals in different regions